Healthcare worker perspectives on adaptations to differentiated anti-retroviral therapy delivery during COVID-19 in South Africa: A qualitative inquiry. - Kwena Tlhaku; Lindani Msimango; Yukteshwar Sookrajh; Cecilia Milford; Pedzisai Munatsi; Andy Gray; Munthra Maraj; Nigel Garrett; Jienchi Dorward (PLOS Global Public Health)
During the COVID-19 pandemic, the South African Centralized Chronic Medicines Dispensing and Distribution (CCMDD) programme, adapted to include extended 12-month antiretroviral therapy (ART) prescriptions, 3-months ART refills and earlier eligibility criteria at 6-months after ART initiation. We aimed to explore the experiences of healthcare workers (HCWs) in implementing these adaptations, and to understand the overall impact of COVID-19 on CCMDD. We conducted semi-structured in-depth interviews with HCWs in eThekwini District clinics, KwaZulu-Natal, South Africa. Interviews were audio-recorded, transcribed, translated, and analysed thematically. Between 18 February and 13 December 2022, we conducted 21 interviews with nurses, doctors, pharmacists, clinic managers and a community pick-up-point staff member. There were mixed perceptions about COVID-19 adaptations to CCMDD. HCWs reported that COVID-19 adaptations to CCMDD helped keep clients away from clinics, reducing exposure to COVID-19, minimizing queues, alleviating client frustration, and easing workload, which enabled more focused attention on clients with greater needs. Clients reportedly preferred 12-month prescriptions as it gave them independence. However, HCWs were concerned about clients' ART adherence, potential to miss out on clinical input, and difficulties aligning annual viral load results, during the 12 months without clinic attendance. The extended eligibility and multi-month dispensing were acceptable to HCWs, but concerns were expressed about non-adherence and stock shortages. Challenges, including staff shortages due to sickness, increased workload, inadequate training, HCWs' distrust in clients' ability to manage their health autonomously, and staff's limited involvement in decisions about the adaptations, impacted on their implementation. While HCWs reported benefits of 12-month prescribing, extended eligibility and multi-month dispensing in CCMDD, long-term implementation would require addressing concerns about impacts on adherence, alignment of annual viral loads and timely follow up. Prioritizing HCW input in decision-making processes and enhancing provider-client interactions will be pivotal in ensuring the effectiveness of CCMDD adaptations.